A comparison of prostate health index, total PSA, %free PSA, and proPSA in a contemporary US population—The MiCheck-01 prospective trial - Shore, Neal D.; Pieczonka, Christopher M.; Henderson, R. Jonathan; Bailen, James L.; Saltzstein, Daniel R.; Concepcion, Raoul S.; Beebe-Dimmer, Jennifer L.; Ruterbusch, Julie J.; Le, Thao Ho; Levin, Rachel A.; Wissmueller, Sandra; Prah, Philip; et al. (Urologic oncology, 2020)
•Contemporary US trial collecting subjects presenting for biopsy due to elevated prostate specific antigen (PSA).•Confirms trend towards more subjects presenting with aggressive prostate cancer.•Prostate health index, PSA, and %free PSA tests were performed for all subjects.•Tests were equivalent at differentiating aggressive and nonaggressive prostate cancer. Increasing numbers of patients are presenting with aggressive prostate cancer (CaP); therefore, there exists a need to optimally identify these patients pre-biopsy. To compare the accuracy of total prostate specific antigen (PSA), %free PSA, and prostate health index (PHI) to differentiate between patients without CaP, with non-aggressive (Gleason 3 + 3, non-AgCaP) and with aggressive (Gleason ≥ 3 + 4, AgCaP) in a contemporary US population. Serum samples were collected from 332 US patients scheduled for biopsy due to an elevated age-adjusted PSA. Site and Central biopsy pathologic assessment were performed. Testing of PSA, free PSA, proPSA, and PHI was performed along with central pathology review. Test performance using logistic regression analysis for differentiating CaP from non-CaP as well as non-AgCaP from AgCaP was evaluated. Central pathology review resulted in 32 upgrades including 14 Gleason 3 + 3 scores being upgraded to AgCaP with final distribution of 148 no-CaP, 64 non-AgCaP, and 120 AgCaP patients. Receiver operator curve (ROC) analysis of the different tests showed that PHI performed best at differentiating CaP from no-CaP subjects (area under the receiver operator curve 0.79). In contrast, the different tests were essentially equivalent in differentiating AgCaP vs. non-AgCaP. In this recent US study of prebiopsy patients we observed a high proportion of AgCaP patients consistent with previous studies in contemporary US populations. Central Gleason review is recommended for multi-institutional studies comparing biomarkers. PHI was superior to PSA, free PSA, %free PSA, and proPSA in detecting CaP in this population but was not superior at differentiating AgCaP from non-AgCaP.